(untitled) (Annual of the Faculty of Philosophy in Skopje, 2019)
Since the beginning of 2015, Europe has been facing a refugee crisis where thousands of people have risked their lives to reach European soil. European politicians and media labelled this crisis as a new issue for the EU, not because the crisis was an entirely new phenomenon, but due to the staggering increase in the number of refugees from conflict areas, most notably Syria, Afghanistan, Eritrea, and Somalia. In 2015 alone, over one million refugees sought asylum in Western Europe. The majority of these had travelled through Turkey, Greece, and the Western Balkans to reach their final destination. The perils they faced during that route have been recorded in many of the reports by the International organization for migration (IOM), the UN Security Council, and many other organizations and departments involved in the crisis. In spite of all this, very little attention has been paid to the gender dimension of this refugee crisis, the problems women have been facing, the treatment they have been given, and the steps taken to help protect their human rights above all, but also their rights to services directly meeting their specific needs.